2002
DOI: 10.4049/jimmunol.169.4.2026
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Toll-Like Receptors in C-C Chemokine Production by Renal Tubular Epithelial Cells

Abstract: Pyelonephritis, in which renal tubular epithelial cells are directly exposed to bacterial component, is a major predisposing cause of renal insufficiency. Although previous studies have suggested C-C chemokines are involved in the pathogenesis, the exact source and mechanisms of the chemokine secretion remain ambiguous. In this study, we evaluated the involvement of Toll-like receptors (TLRs) in C-C chemokine production by mouse primary renal tubular epithelial cells (MTECs). MTECs constitutively expressed mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
198
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(212 citation statements)
references
References 51 publications
12
198
1
1
Order By: Relevance
“…However, UPECs that stimulate the expression of RANTES in whole kidneys did not activate its expression in cultured MCDs. LPS has been shown to stimulate the production of both MCP-1 and RANTES in cultured mouse primary renal proximal tubule cells (21). Although the NF-B activation seems to be essential for LPS-mediated up-regulation of these two chemokines, the inhibition of JNK and p38 MAPK impairs the expression of RANTES but not of MCP-1 (21), suggesting that RANTES and MCP-1 are differently regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, UPECs that stimulate the expression of RANTES in whole kidneys did not activate its expression in cultured MCDs. LPS has been shown to stimulate the production of both MCP-1 and RANTES in cultured mouse primary renal proximal tubule cells (21). Although the NF-B activation seems to be essential for LPS-mediated up-regulation of these two chemokines, the inhibition of JNK and p38 MAPK impairs the expression of RANTES but not of MCP-1 (21), suggesting that RANTES and MCP-1 are differently regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using the hemopoietic chimeric Lps n and Lps d mice demonstrated that bladder epithelial cells (19), as well as intrinsic renal epithelial cells (20), contribute together with bone marrow-derived cells to the initiation of antibacterial immunity. Murine and human renal tubule cells express some of the TLR expressed in hemopoietic cells and secrete chemokines upon LPS stimulation (21,22). In addition, TLR2 and TLR4 have been shown to be up-regulated in the distal nephron of inflamed, postischemic, reperfused kidneys (23).…”
Section: Renal Collecting Duct Epithelial Cells React Tomentioning
confidence: 99%
“…These staining patterns were the same as those previously reported. 40 Subconfluent tubular epithelial cells were incubated in serum-free medium for 24 hours to arrest and synchronize cell growth. After that, the medium was changed to fresh serum-free DMEM containing 5 ng/ml recombinant TGF-␤ (R&D Systems) for 0, 1, 3, 6, 12, and 24 hours in the time-course study.…”
Section: Cell Culturementioning
confidence: 99%
“…TLR2 can be found on professional immune cells, including neutrophils, macrophages, and dendritic cells, but also on stromal cells throughout the body (14). Within the kidney, mRNA for TLR2 has been isolated from mouse renal tubular epithelial cells, and in situ hybridization has shown the presence of TLR2 in tubular epithelial cells and also within the glomerulus (15,16).…”
mentioning
confidence: 99%